2014
DOI: 10.1001/jamapediatrics.2014.1560
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age at Virologic Control on Peripheral Blood Human Immunodeficiency Virus Reservoir Size and Serostatus in Perinatally Infected Adolescents

Abstract: Importance Combination antiretroviral therapy (cART) initiated within several weeks of HIV infection in adults limits proviral reservoirs that preclude HIV cure. Biomarkers of restricted proviral reservoirs may aid in the monitoring of HIV remission or cure. Objectives To quantify peripheral blood proviral reservoir size in perinatally HIV-infected adolescents and to identify correlates of limited proviral reservoirs. Design, Setting, and Participants A cross-sectional study including 144 perinatally HIV-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
74
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 34 publications
11
74
0
1
Order By: Relevance
“…Younger age at starting ART in children has been found to be strongly related to the size of the viral reservoir. 1821 One study reported that reduced reservoir size was observed in children who suppressed by 12 months of age. 18 Age at viral control is a more complex characteristic to compare between groups as it depends on the frequency of viral load testing once ART is started as well as the age when ART is started.…”
Section: Discussionmentioning
confidence: 99%
“…Younger age at starting ART in children has been found to be strongly related to the size of the viral reservoir. 1821 One study reported that reduced reservoir size was observed in children who suppressed by 12 months of age. 18 Age at viral control is a more complex characteristic to compare between groups as it depends on the frequency of viral load testing once ART is started as well as the age when ART is started.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest HIV DNA levels were observed in patients who had low baseline levels and who received early treatment (107). In children, the HIV DNA level was markedly lower when viral control was achieved before age 1 year than between the ages of 1 and 5 years or after age 5 years (73). This difference is linked to the duration of uncontrolled viral replication between initial infection and effective treatment.…”
Section: Time From Hiv-1 Infection To Treatment Initiation Influencesmentioning
confidence: 96%
“…More recently, an assay that dispenses with the extraction step has been proposed (70). Recent technical progress has permitted the development of HIV DNA quantification by digital droplet PCR (ddPCR), which does not require an external quantification standard (71)(72)(73)(74)(75)(76)(77). However, some false-positive signals have been observed with ddPCR, which can be a problem when this method is used for diagnosis (76).…”
Section: Dna Load In Resting Cd4mentioning
confidence: 99%
“…Importantly, it was recently argued by Klein et al (95) that children are ideal candidates for immunotherapeutic interventions to achieve viral remission. The arguments presented by the authors are based on the fact that perinatally infected children for whom antiretroviral (ARV) treatment is initiated early on have a small latent virus reservoir (96,97) and normal development of the memory B cell and T cell compartments (98,99). The potential for viral eradication in children was recently illustrated by the "Mississippi baby."…”
Section: Hiv Vaccine Responses In Infants and Adultsmentioning
confidence: 99%